An inflammatory bowel disease-associated SNP increases local thyroglobulin expression to develop inflammation in miniature dachshunds - Teoh, Yong Bin; Jiang, Jing-Jing; Yamasaki, Takeshi; Nagata, Noriyuki; Sugawara, Toshiki; Hasebe, Rie; Ohta, Hiroshi; Sasaki, Noboru; Yokoyama, Nozomu; Nakamura, Kensuke; Kagawa, Yumiko; Takiguchi, Mitsuyoshi; et al. (Frontiers in Veterinary Science, 2023)
Inflammatory colorectal polyp (ICRP) in Miniature Dachshund (MDs) is a chronic inflammatory bowel disease (IBD) characterized by granulomatous inflammation that consists of neutrophil infiltration and goblet cell hyperplasia in the colon. Recently, we previously identified five MDassociated single nucleotide polymorphisms (SNP), PLG, TCOF1, TG, COL9A2, and COL4A4, by whole-exome sequencing. Here we investigated whether TG c.4567C>T (p.R1523W) is associated with the ICRP pathology. We found that the frequency of the T/T SNP risk allele is significantly increased in MDs with ICRP. In vitro experiments showed that TG expression in nonimmune cells was increased by inducing the IL-6 amplifier with IL-6 and TNF-α. On the other hand, a deficiency of TG suppressed the IL-6 amplifier. Moreover, recombinant TG treatment enhanced activation of the IL-6 amplifier, suggesting that TG is both a positive regulator and target of the IL-6 amplifier. We also found that TG expression together with two NF-κB targets, IL6 and CCL2, was increased in colon samples isolated from MD with the T/T risk allele compared to those with the C/C non-risk allele, but serum TG was not increased. Cumulatively, these results suggest that the T/T SNP is an expression quantitative trait locus (eQTL) of TG mRNA in the colon and local TG expression triggered by this SNP increases the risk of ICRP in MDs via the IL-6 amplifier. Therefore, TG c.4567C>T is a diagnosis target for ICRP in MDs and TG-mediated IL-6 amplifier activation in the colon is a possible therapeutic target for ICRP.